21.16 cups of flour just divide 127 by 6
Answer:
![(f-g)(x)=2x-3](https://tex.z-dn.net/?f=%28f-g%29%28x%29%3D2x-3)
Step-by-step explanation:
<em>The correct question is</em>
If f(x)=3x-1 and g(x)=x+2, find (f-g)(x)
we know that
(f-g)(x) is equal to subtract the function g(x) from the function f(x)
so
![(f-g)(x)=f(x)-g(x)](https://tex.z-dn.net/?f=%28f-g%29%28x%29%3Df%28x%29-g%28x%29)
substitute the given functions
![(f-g)(x)=(3x-1)-(x+2)](https://tex.z-dn.net/?f=%28f-g%29%28x%29%3D%283x-1%29-%28x%2B2%29)
Remove the parenthesis
![(f-g)(x)=3x-1-x-2)](https://tex.z-dn.net/?f=%28f-g%29%28x%29%3D3x-1-x-2%29)
Combine like terms
![(f-g)(x)=2x-3](https://tex.z-dn.net/?f=%28f-g%29%28x%29%3D2x-3)
Answer:the first one
Step-by-step explanation:
i am teacher lol
Answer:
3
Step-by-step explanation:
Given
f(x) =
, then
f(12) =
=
= ± 3
There are 2 values 3 and - 3
The positive value of f(12) is + 3